Performance analysis of handover parameter for natural disaster in LTE-A network - Azita Laily Yusof; Ainnur Eiza Mohd Azhar; Norsuzila Ya’acob (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Natural disaster is an unpredictable event which can cause service communication disruption. The disruption of service communication can be divided into three cases which are power outage, broken backhaul and physical destruction by disaster. This paper focuses on power outage case. Although each base stations equipped with backup batteries, it only last for several hours. After natural disaster hit certain areas, traffic is highly congested due to panic and rescue operation of lifesaving. This scenario will drain the backup batteries quickly. In order to limit the UEs’ connection to the affected base station, this research proposed to adjust Received Signal Strength (RSS) based on parameter called as a distance fraction coefficient, α so that the affected coverage area is reduced when in disaster area situation. The parameter is added in the path loss equation and later in the RSS equation. The numerical results show the RSS improved whereby α=0.2 gives the optimal value and therefore limit the incoming traffic to the affected base station.